Development of Learning Media Using PMRI-Based Scratch Applications for Statistics Material for Class VIII Junior High School - Shelly Gustia Putri; Dona Ningrum Mawardi; Maria Luthfiana (jurnal matematika, 2026)
Purpose of the study: This study aims to develop interactive learning media using the Scratch application based on the Indonesian Realistic Mathematics Approach (PMRI) for Statistics material for eighth-grade junior high schools. It also examines the validity, practicality, and effectiveness of the developed media in mathematics learning.. Methodology:This study used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop Scratch-based learning media based on the Indonesian Realistic Mathematics Education (PMRI) approach for Statistics. The instruments used consisted of expert validation sheets, teacher and student response questionnaires, and pretest-posttest learning achievement tests. Data were analyzed using descriptive quantitative methods with a five-point Likert scale. Main Findings: The developed Scratch-based PMRI learning media on Statistics achieved a material expert validity score of 0.88, a media expert score of 0.90, and a language expert score of 0.83. Teacher and student responses indicated the media was highly practical. Pretest and posttest results showed improved student learning outcomes, indicating that the media was valid, practical, and potentially effective for mathematics learning. Novelty/Originality of this study: The novelty of this research lies in the integration of the Scratch application with the PMRI approach in developing interactive learning media for Statistics. The developed media incorporates real-life contexts and student-centered learning activities, thereby supporting more meaningful and engaging mathematics learning and enhancing student engagement.